2000
DOI: 10.1590/s0100-879x2000000400003
|View full text |Cite
|
Sign up to set email alerts
|

Connexin hemichannels and cell-cell channels: comparison of properties

Abstract: Connexin46 (Cx46) forms functional hemichannels in the absence of contact by an apposed hemichannel and we have used these hemichannels to study gating and permeation at the single channel level with high time resolution. Using both cell-attached and -excised patch configurations, we find that single Cx46 hemichannels exhibit some properties expected of half of a gap junction channel, as well as novel properties. Cx46 hemichannels have a large unitary conductance (~300 pS) and a relatively large pore as inferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 19 publications
4
36
0
2
Order By: Relevance
“…An AFM equipped with a buffer chamber allowed us to observe Cx26 membranes under native conditions at high resolution. Analogous to the TSF system of Harris et al (37) or the excised patch experiments of Verselis et al (38), this is a reductionist system. We limit the number of variables in the imaging experiment, which makes our results complementary to the pH studies done in whole cells (12,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An AFM equipped with a buffer chamber allowed us to observe Cx26 membranes under native conditions at high resolution. Analogous to the TSF system of Harris et al (37) or the excised patch experiments of Verselis et al (38), this is a reductionist system. We limit the number of variables in the imaging experiment, which makes our results complementary to the pH studies done in whole cells (12,39).…”
Section: Discussionmentioning
confidence: 99%
“…For cardiac connexins (Cx43, Cx40, and Cx45), Delmar and co-workers (12) demonstrated that truncation of the C terminus significantly decreased the response of the intact channels to acidification. In a study comparing Cx46 channels and hemichannels expressed in oocytes, and using excised patches of Cx46 hemichannels, Verselis and coworkers (19,38) showed that Cx46 hemichannels act similarly to intact channels and close reversibly with acidification. The site of action for H ϩ is localized to the cytoplasmic domains.…”
Section: Volume 282 • Number 12 • March 23 2007mentioning
confidence: 99%
“…An open hemichannel could well exhibit asymmetry in fixed charges that causes rectification, whereas the asymmetry is neutralized in the cell-cell channel [45,51].…”
Section: What Opens Hemichannels?mentioning
confidence: 99%
“…Given this, connexin hemichannels may release ATP as part of an apoptosis pathway. Consistent with this possibility, Cx46 hemichannels open under physiological conditions (213,268,282), an intriguing notion given the upregulation of Cx46 in response to lung injury (described below). The notion of functional roles for connexin hemichannels is being further explored, as this is still a controversial area in need of further study.…”
Section: Connexin Hemichannels As Plasma Membrane Channelsmentioning
confidence: 76%
“…This has led to the suggestion that connexin hemichannels at the cell surface might mediate ATP release directly from the cytosol to the extracellular environment (54,257). Permeability from connexin hemichannels, by and large, seems to reflect the permeability of complete gap junction channels and thus could certainly enable ATP diffusion (88,171,268,282). However, it is still feasible that cells might use a different plasma membrane channel for mediating ATP release that nonetheless requires cell-cell coupling through gap junctions.…”
Section: Connexin Hemichannels As Plasma Membrane Channelsmentioning
confidence: 99%